Deformation and failure processes of kaolinite under tension: Insights from molecular dynamics simulations - Yang, H.; He, M.; Lu, Chunsheng; Gong, W. (Zhongguo Kexue Zazhishe, 2019)
As a primary constituent of soft rocks, kaolinite plays an important role in large deformations of underground structures, which usually leads to serious safety risks. This paper investigates the deformation and failure processes of kaolinite under tension using molecular dynamics simulations. Based on the atomistic scale of these deformation and failure processes and their stressstrain curves, Young’s moduli and strengths in three crystal directions and the surface energy of the (001) plane were obtained, which were consistent with theoretical predictions. The number of broken bonds and their corresponding broken sequences were determined. The results of our study indicated that as more bonds break during tension, the initiation of crack led to a sharp decrease in stress. We also explored the influence of temperature on the mechanical properties of kaolinite, which indicated that as temperature increased, the tensile strength and Young’s modulus decreased.